2019
DOI: 10.3390/insects10070185
|View full text |Cite
|
Sign up to set email alerts
|

Foraging Macrotermes natalensis Fungus-Growing Termites Avoid a Mycopathogen but Not an Entomopathogen

Abstract: Fungus-growing termites have to defend both themselves and their monoculture fungal cultivars from antagonistic microbes. One of the ways that pathogens can enter the termite colony is on the plant substrate that is collected by termite foragers. In order to understand whether foragers avoid substrate infected with antagonists, we offered sub-colonies of Macrotermes natalensis a choice between food exposed to either a mycopathogenic or an entomopathogenic fungus, and control food. Workers did not show any pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
0
13
0
1
Order By: Relevance
“…Sorokin strain NRRL 30905 was repellent against C. formosanus in different substrates (sand, soil, and sawdust). Bodawatta et al [39] reported that the fungus-growing termite Macrotermes natalensis (Haviland) did not avoid substrate containing the entomopathogenic fungus Beauveria bassiana (Balsamo) Vuillemin isolate #122. Mburu et al [14,15] reported that the repellency of entomopathogenic fungi was determined by their virulence, volatiles, and genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Sorokin strain NRRL 30905 was repellent against C. formosanus in different substrates (sand, soil, and sawdust). Bodawatta et al [39] reported that the fungus-growing termite Macrotermes natalensis (Haviland) did not avoid substrate containing the entomopathogenic fungus Beauveria bassiana (Balsamo) Vuillemin isolate #122. Mburu et al [14,15] reported that the repellency of entomopathogenic fungi was determined by their virulence, volatiles, and genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of complementary defence mechanisms appear to contribute to keep fungus gardens free from other fungi [ 8 , 28 ]. These include termites avoiding antagonists [ 29 ], burying unwanted fungi [ 30 ], and utilising antimicrobial chemical compounds of termite [ 22 ], Termitomyces [ 8 , 31 , 32 ] and bacterial [ 8 , 20 , 33 , 34 ] origins. In addition, it has been proposed that the obligate first gut passage of all plant substrate used to manure the fungus could serve as a filtering—potentially fungicidal step—accounting for the very low prevalence of non- Termitomyces fungi within fungus combs [ 16 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The success of termite fungiculture depends on multiple factors, such as the control of pathogens within termite fungus farms, termite antimicrobial peptides and gut bacteria with antimicrobial properties ( Um et al, 2013 ; Poulsen, 2015 ; Bodawatta et al, 2019 ). The results in this study revealed that fungus-growing termite M. barneyi -associated actinomycetes produced different type of polyenes, which greatly inhibited competitor fungus Xylaria sp.…”
Section: Discussionmentioning
confidence: 99%